PHYSIOANATOMICAL ASPECTS OF KURMASANA: - A REVIEW STUDY - Choudhary, Dharmendra; Yadav, Sunil Kumar; Samagandi, kashinath (International Research Journal of Ayurveda & Yoga, 2024)
Asana are not just physical exercises, they have biochemical, psychophysiological and psychospiritual effects. The study of anatomy is integral to the proper practice of Asana. Additionally, for Yoga practitioner’s anatomical awareness is a powerful tool for keeping their body free from all sorts of jerks, injury and pain. Knowledge of anatomy of Asana enables everyone to adopt and practice suitable Asana based on physical or skeletal structure. Practice of Kurmasana can activate the Moola Bandha.